Taurine treatment protects against chronic nicotine-induced oxidative changes - ŞENER, GÖKSEL; ÇETİNEL, ŞULE (WILEY, 2005)
Experiments have shown that chronic nicotine administration caused oxidative damage in various organs by increasing lipid peroxidation products and decreasing the activity of endogenous antioxidants. The aim of this study was to investigate the effects of taurine treatment on nicotine-induced oxidative changes in rat thoracic aorta and heart and to explore the possible mechanisms of action. Male Wistar albino rats (200-250 g) were injected with nicotine hydrogen bitartrate (0.6 mg/kg; i.p.) or saline for 21 days. Taurine was administered (50 mg/kg; i.p.) alone or along with nicotine injections. After decapitation, the thoracic aorta and heart tissues were excised. The aorta was used for in vitro contractility studies or stored along with the heart samples for the measurement of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen content. Tissue samples were also examined histologically. Serum samples were stored for the measurement of MDA, GSH and lactate dehydrogenase (LDH) activity. Chronic nicotine treatment impaired both the contraction and relaxation responses of the aortic rings to phenylephrine and acetylcholine, respectively. It increased lipid peroxidation, MPO levels and tissue collagen content of both aorta and heart samples. Taurine supplementation to nicotine-treated animals reversed the contractile dysfunction and restored the endogenous GSH levels and decreased high lipid peroxidation and MPO activities in both tissues. These data suggest that taurine supplementation effectively attenuates the oxidative damage because of chronic nicotine administration possibly by its antioxidant effects.
Keywords: neutrophil; nicotine; oxidative damage; rat; taurine; DEPENDENT ARTERIOLAR DILATATION; INFLAMMATORY MEDIATORS; SUPEROXIDE-DISMUTASE; FANCONI-SYNDROME; NITRIC-OXIDE; IN-VITRO; RATS; STRESS; MYELOPEROXIDASE; ENDOTHELIUM